PERAN ISTRI SEBAGAI PENCARI NAFKAH UTAMA DI KOTA LANGSA MENURUT HUKUM ISLAM - Asyraf Kamil Pasha; Muliadi Kurdi; Bustamam Usman (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2024)
This study examines the role of wives as the primary breadwinners according to Islamic law in Kota Langsa. The background of this research is the changing gender roles in modern society, leading to an increasing number of wives serving as the primary earners in their families. This phenomenon arises due to various factors, including the husband's inability to meet the family's needs due to health issues, financial limitations, or the wife's higher earning potential. Additionally, social and economic developments have driven changes in the perception of traditional roles within the household, making it more acceptable for wives to work and contribute to the family's economy. However, these changes also bring about challenges and debates regarding the compatibility of these roles with religious and cultural values and norms. The research questions addressed include: what factors lead wives to become the primary breadwinners in Kota Langsa, what is the perspective of Islamic law on wives as primary earners, and what is the relationship dynamic of wives who play the main role in earning a living for their families. The research method used is a qualitative approach with thematic data analysis techniques. Data were collected through in-depth interviews with various respondents, including husbands and wives in Kota Langsa, as well as religious and community leaders. The results of the study indicate significant support for the concept of wives working and becoming the primary breadwinners, especially in situations where the husband is unable to fulfill his financial obligations. However, there are also views that reject this concept, arguing for the preservation of the traditional role of the husband as the main provider. The conclusion of this study is that there are clear differences in opinions regarding the role of wives as primary breadwinners. These differences reflect the social and cultural dynamics in Kota Langsa, as well as the importance of cooperation and communication between husbands and wives in fulfilling their respective roles. This research is expected to contribute to the discussion on gender equality and the division of responsibilities within the family according to Islamic law.